Intergenerational Occupational Mobility Among Men in Iran During 1996-2016 - Mohammad Hoseini (برنامه‌ریزی و بودجه, 2019)
This paper documents the changes in intergenerational occupational mobility among men in Iran for the last two decades. To measure intergenerational mobility, the Altham distance between the job transition matrices has been used for during the period in question. The results suggest that for the period (1996-2011), occupational mobility declined; this downward trend is steeper in 2006-2011, and it has leveled off until 2016. One of the factors that explains this decrease in occupational mobility is the flat supply of public sector jobs. In the period in question, while active population increases by more than 10 million, the public sector jobs rise by less than 1 million, bringing about a higher level of competition for obtaining those jobs. The analysis shows that following this phenomenon, the chance for obtaining public sector job has increased greatly for those whose father had a public sector job. In addition, jobless growth and higher education boom are two potential reasons for the sharper reduction in mobility during 2005-2011.